2018
DOI: 10.4103/ijabmr.ijabmr_333_16
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of multidrug-resistant, Class I and II integrons and molecular typing of CTX-M-producing Klebsiella pneumoniae

Abstract: Introduction:Klebsiella pneumoniae (K. pneumoniae) is an important opportunistic pathogen causes serious community and hospital-acquired infections, which is highly resistant to antibiotics. We aimed to determine the frequency of multidrug resistant (MDR) and molecular typing of clinical isolates of K. pneumoniae.Methodology:One hundred isolates of K. pneumoniae were collected from clinical samples in three general hospitals in Kermanshah. The antimicrobial susceptibility and extended-spectrum beta-lactamases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…pAmpC beta lactamase genes were reported by two studies in clinical isolates of Klebsiella pneumoniae (Mansouri et al, 2012; Kiaei et al, 2018). PFGE and ERIC-PCR analysis in these studies showed the presence of different clones in each clinical center (Akya et al, 2018; Hashemizadeh et al, 2018; Kiaei et al, 2018; Maleki et al, 2018). This is with the exception of one study where high clonal relatedness among ESBL K. pneumoniae strains was reported (Ghaffarian et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 68%
See 1 more Smart Citation
“…pAmpC beta lactamase genes were reported by two studies in clinical isolates of Klebsiella pneumoniae (Mansouri et al, 2012; Kiaei et al, 2018). PFGE and ERIC-PCR analysis in these studies showed the presence of different clones in each clinical center (Akya et al, 2018; Hashemizadeh et al, 2018; Kiaei et al, 2018; Maleki et al, 2018). This is with the exception of one study where high clonal relatedness among ESBL K. pneumoniae strains was reported (Ghaffarian et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 68%
“…In Iran, studies have shown that in Klebsiella spp., resistance to extended spectrum beta lactams is mainly mediated via the production of CTX-M variants (CTX-M-15, CTX-M-3, CTX-M-8, CTX-M-1, and CTX-M-2) (Feizabadi et al, 2010; Peerayeh et al, 2014; Bialvaei et al, 2016; Akya et al, 2018; Dehshiri et al, 2018) and to a lesser degree via SHV (SHV-12, SHV-11, SHV-5) (Feizabadi et al, 2010; Shakib et al, 2018), TEM genes (Gholipour et al, 2014; Maleki et al, 2018) and others (VEB, PER, and GES) (Sedighi et al, 2017). pAmpC beta lactamase genes were reported by two studies in clinical isolates of Klebsiella pneumoniae (Mansouri et al, 2012; Kiaei et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…Likewise, other US study on Enterobacteriaceae isolates obtained from fish, poultry, swine and cattle reported that 52% of them contained either class 1 or class 2 integrases, with the frequencies of 46% intI 1, 6% intI 2 and 5% intI 1 plus intI 2 [62]. Additionally, another study performed on MDR K. pneumoniae isolates from Iranian hospitals showed similar trends regarding the prevalence of the two integrons classes and a positive association between the class 1 integrons and MDR [63]. A Polish investigation on clinical samples from patients not undergoing AB therapy and from a WWTP detected 12.1% of the E. coli isolates with integrase genes, 10.9% of which with class 1, 1.4% with class 2 and 0% with class 3 [64].…”
Section: Resultsmentioning
confidence: 89%
“…These strains were seen to be genetically diverse, with phenotypic differences in their susceptibility to antimicrobials. As in our study, findings regarding genetic diversity in isolates have varied among researchers [ 69 , 70 , 71 , 72 ]. Additionally, the PFGE results in the present study revealed no specific pattern of association between pulsotype cluster analyses and the resistant phenotypes of the isolates, which may be a reflection of the genomic characteristics of this Gram-negative opportunistic pathogen in which the plasmid genome and chromosomal genes are large (as previously documented [ 59 ]).…”
Section: Discussionmentioning
confidence: 65%